SNP rs6564851 in the BCO1 gene is associated with varying provitamin A plasma concentrations but not with retinol concentrations among adolescents from rural Ghana - Graßmann, Sophie; Pivovarova-Ramich, Olga; Henze, Andrea; Raila, Jens; Ampem Amoako, Yaw; King Nyamekye, Richard; Bedu-Addo, George; Mockenhaupt, Frank P.; Schulze, Matthias B.; Danquah, Ina (Nutrients, 2020)
In sub-Saharan Africa, vitamin A deficiency constitutes a severe health problem despite various supplementation and food fortification programs. Given that the intake of preformed vitamin A from animal products remains low in these countries, an efficient metabolization of plant-based provitamin A carotenoids is essential. Previously, adolescents in rural Ghana have shown high total plasma carotenoid concentrations, while 36% had a vitamin A deficiency (defined as plasma retinol < 0.7 µmol/L). Hence, the aim of this cross-sectional study was to identify the relationships between variants in the β-carotene 15,15’-oxygenase (BCO1) gene and plasma carotenoid concentrations among 189 15-year-old girls and boys in rural Ghana. BCO1 rs6564851, rs7500996, rs10048138 and PKD1L2 rs6420424, and rs8044334 were typed, and carotenoid concentrations were compared among the different genotypes. G allele carriers of rs6564851 (53%) showed higher plasma carotenoid concentrations than T allele carriers (median (interquartile range): 3.07 (2.17-4.02) vs. 2.59 (2.21-3.50) µmol/L, p-value = 0.0424). This was not explained by differences in socio-demographic or dietary factors. In contrast, no differences in plasma retinol concentrations were observed between these genotypes. Pending verification in independent populations, the low conversion efficiency of provitamin A carotenoids among rs6564851 G allele carriers may undermine existing fortification and supplementation programs to improve the vitamin A status in sub-Saharan Africa.
Gesehen am 14.09.2020